Factores que influyen en la intención de emprendimiento del emprendedor híbrido - Gonzales Peralta, Patricia (Pontificia Universidad Católica del Perú, 2021)
From the theory of planned behavior, factors are proposed that would influence the intention of entrepreneurship in the second stage of hybrid entrepreneurship. This conceptual research makes use of secondary information for thematic analysis of the literature. In this way, a conceptual model and propositions are established. As a result, four factors that influence this intention are determined: The expectation of business growth, entrepreneurial social capital, organizational commitment with the employer and entrepreneurial self-efficacy. Finally, the study has three contributions. First, it offers a multidisciplinary approach by applying the theory in a new context; second, it offers propositions related to the hypotheses of a new conceptual model for subsequent empirical evaluation; and, third, it promotes the visibility of the hybrid entrepreneur in the public policy literature in support of entrepreneurship.

A partir de la teoría del comportamiento planeado, se proponen factores que influirían en la intención de emprendimiento en la segunda etapa del emprendimiento híbrido. Esta investigación conceptual hace uso de información secundaria para el análisis temático de la literatura. De esta manera, se establecen un modelo conceptual y proposiciones. Como resultado, se determinan cuatro factores que influenciarían dicha intención: la expectativa de crecimiento empresarial, el capital social emprendedor, el compromiso organizacional con el empleador y la autoeficacia emprendedora. Finalmente, el estudio tiene tres contribuciones. Primero, ofrece un enfoque multidisciplinario al aplicar la teoría del comportamiento planeado en un nuevo contexto; segundo, plantea proposiciones en un nuevo modelo conceptual para su evaluación empírica posterior; y, tercero, promueve la visibilidad del emprendedor híbrido en la literatura.
Keywords: Hybrid entrepreneurship; Theory of planned behavior; Emprendimiento híbrido; Entrepreneurship intention; Teoría del comportamiento planeado; Resignation of employment; Intención de emprendimiento; Renuncia al empleo; Promotion of entrepreneurship; Fomento al emprendimiento; https://purl.org/pe-repo/ocde/ford#5.02.04